Likelihood of Discovering a CSF Leak Based on Intracranial MRI Findings in Patients without a Spinal Longitudinal Extradural Collection: A New Probabilistic Scoring System - Benson, John C.; Madhavan, Ajay A.; Mark, Ian T.; Cutsforth-Gregory, Jeremy K.; Brinjikji, Waleed; Verdoorn, Jared T. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: The likelihood of discovering a CSF leak can be determined by assessing intracranial abnormalities. However, the Dobrocky scoring system, which is used to determine this likelihood, did not incorporate patients with CSF-venous fistulas. This study sought to create a new probabilistic scoring system applicable to patients without a spinal longitudinal extradural collection.MATERIALS AND METHODS: A retrospective review was completed of patients with suspected spontaneous intracranial hypotension who underwent brain MR imaging followed by digital subtraction myelography with same-day CT myelography. Patients with and without leaks found on digital subtraction myelography were included. MRIs were assessed for numerous reported stigmata of spontaneous intracranial hypotension and were compared between cohorts.RESULTS: One hundred seventy-four patients were included; 113 (64.9%) were women (average age, 52.0 [SD, 14.3] years). A CSF leak was found in 98 (56.3%) patients, nearly all of which (93.9%) were CSF-venous fistulas. Diffuse dural enhancement, internal auditory canals dural enhancement, non-Chiari cerebellar descent, pituitary engorgement, brain sag, dural venous sinus engorgement, and decreased suprasellar cistern size were associated with a CSF leak. A probabilistic scoring system was made in which a single point value was assigned to each of those findings: 0–2 considered low probability and ≥3 considered intermediate-to-high probability of a CSF leak.CONCLUSIONS: This study offers a new probabilistic scoring system for evaluating the likelihood of discovering a CSF leak on the basis of intracranial MR imaging findings, though the new system is not superior to that of the Dobrocky method for predicting the presence of CSF leaks.AUCarea under the curveCTMCT myelographyDSMdigital subtraction myelographyIACinternal auditory canalSIHspontaneous intracranial hypotensionSLECspinal longitudinal extradural fluid collection